Evaluation of Virgin Coconut Oil Concentration Variations in Emulgel Formulations of Garlic (Allium sativum L.) Extract as an Antibacterial Hand Sanitizer - Rohmani, Sholichah; Fitria, Krismona Rizky Nur; Utami, Diyah Tri; Susanto, Nindita Clourisa Amaris; Ermawati, Dian Eka; Sasongko, Heru; Zulpadly, M. Fiqri; Darojati, Ulfa Afrinurfadhilah; Meitasari, Annisa Diyan; Aratanti, Anif Nur; Untari, Meta Kartika (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
One of the effective ways to stay healthy is maintaining cleanliness, including hand hygiene. Various diseases can be easily transmitted through the hands. However, modern developments have changed the habit of handwashing with water to using hand antiseptics. Hand sanitizer is an alternative to overcome this problem. Unfortunately, some hand sanitizer gels on the market still contain alcohol as an antibacterial ingredient. It is necessary to innovate in making hand sanitizers using non-alcoholic ingredients as antibacterials, for example, natural ingredients like garlic. Garlic contains allicin that functions as an antibacterial. Meanwhile, VCO contains high lauric acid with antibiotic properties that function as antiviral, antibacterial, and antiprotozoal. It also contains capric acid, with antiviral and antibacterial functions. This study aims to examine the effect of concentration variation of VCO on the physical stability of garlic extract emulgel preparation and antibacterial effectiveness against the growth of Staphylococcus aureus. The concentration variation of VCO in this study was 3%, 5%, and 7% for 3 types of formulas. The results showed that the concentration variation of VCO in emulgel preparations gave differences in the physical properties of the gel, including pH, viscosity, adhesive strength, and spreadability. It can be concluded that the higher the VCO concentration, the higher the pH, viscosity, and adhesive power, and the lower the spreadability and antibacterial inhibition power against Staphylococcus aureus. The best result from the evaluation of physicochemical properties and antibacterial tests was Formula 1, although it was still in the weak inhibitory power category.